Erythroxylum cuneatum regulates the cell adaptation through the ERK 1/2 signalling in addictive morphine-induced cell line - Noor Azuin, Suliman; Mohamad Aris, Mohd Moklas; Che Norma, Mat Taib (2020)
Introduction: Chronic treatment of morphine stimulates prolonged activation of the µ-opioid receptor, causes the stimulation of cellular adaptation through ERK 1/2 pathway. The abrupt termination of chronic morphine was observed to cause withdrawal activity through the same pathway. The alkaloid extract of Erythroxylum cuneatum was proposed to have anti-withdrawal properties against morphine, regardless of lacking information on the cellular adaptation. Objectives: The in vitro study, using the neuroblastoma cell line; SK-N-SH, was designed to observe the morphine withdrawal activities in the cellular adaptation perspective against the plant extract and methadone. Materials and Methods: To achieve the objective, the cells were pre-treated with morphine. Meanwhile, to observe the antagonistic activity, the cells were co-treated with morphine and plant extract or morphine with methadone. The protein expression of respective proteins for cellular adaptation; mitogenactivated protein (MAP)/extracellular signal-regulated (ERK) kinase 1/2 (MEK 1/2), extracellular signal-regulated kinase 2 (ERK 2), cAMP-dependent protein kinase (PKA), protein kinases C (PKC), were obtained from western blot technique. Results: The finding showed pre-treated cell with morphine expressed higher content of MEK 1/2, ERK 2, PKA and PKC, as compared to co-treatment of morphine. In regards, the co-treatment and post-treatment of methadone and extract of E. cuneatum were evaluated to normalise the changes affected by morphine, comparable to the control group. Conclusion: E. cuneatum was postulated to have anti-withdrawal property mimicking the methadone and react on the same pathway with methadone and morphine observed through antagonistic activity. E. cuneatum was suggested to normalise the effect of chronic morphine via ERK 1/2 signalling pathway.